Genome complexity in the coelacanth is reflected in its adaptive immune system. Issue 6 (24th January 2014) - Saha, Nil Ratan; Ota, Tatsuya; Litman, Gary W.; Hansen, John; Parra, Zuly; Hsu, Ellen; Buonocore, Francesco; Canapa, Adriana; Cheng, Jan‐Fang; Amemiya, Chris T.; Amemiya, Chris; Meyer, Axel
ABSTRACT We have analyzed the available genome and transcriptome resources from the coelacanth in order to characterize genes involved in adaptive immunity. Two highly distinctive IgW‐encoding loci have been identified that exhibit a unique genomic organization, including a multiplicity of tandemly repeated constant region exons. The overall organization of the IgW loci precludes typical heavy chain class switching. A locus encoding IgM could not be identified either computationally or by using several different experimental strategies. Four distinct sets of genes encoding Ig light chains were identified. This includes a variant sigma‐type Ig light chain previously identified only in cartilaginous fishes and which is now provisionally denoted sigma‐2. Genes encoding α/β and γ/δ T‐cell receptors, and CD3, CD4, and CD8 co‐receptors also were characterized. Ig heavy chain variable region genes and TCR components are interspersed within the TCR α/δ locus; this organization previously was reported only in tetrapods and raises questions regarding evolution and functional cooption of genes encoding variable regions. The composition, organization and syntenic conservation of the major histocompatibility complex locus have been characterized. We also identified large numbers of genes encoding cytokines and their receptors, and other genes associated with adaptive immunity. In terms of sequence identity and organization, the adaptive immune genes of the coelacanth more closely resemble orthologous genes in tetrapods than those in teleost fishes, consistent with current phylogenomic interpretations. Overall, the work reported described herein highlights the complexity inherent in the coelacanth genome and provides a rich catalog of immune genes for future investigations. J. Exp. Zool. (Mol. Dev. Evol.) 322B: 438–463, 2014. © 2014 Wiley Periodicals, Inc.